Penerapan Analisis Cost Volume Profit dalam Pengambilan Keputusan Menajemen pada Usaha Tungku Dakak-Dakak Nila - Rahmi, Mega; Putri, Melati; Sari, Mila Yulia; Naimatulhuda, Naimatulhuda; Rahmadani, Novida; Putra, Yosep Eka (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
Cost volume profit analysis is used in measurable planning in sales and determining the Company's profit based on the relationship between costs, volume and overall profit. This study aims to determine how to apply the cost volume profit method to the Nila Dakak-Dakak Furnace Business. This study uses a quantitative descriptive research method where data collection techniques are carried out through direct interviews with owners and employees, observation and documentation of production and financial data of the Nila Dakak-Dakak Furnace Business. Based on the results of the research that has been carried out, it can be concluded that the Nila Dakak-Dakak Furnace Business made a profit in 2023 of IDR 154,760,000 with sales of IDR 686,400,000. Sales at the break-even point are 2,154 so that if sales are less than that amount, the Company will experience a loss. For this reason, a margin of safety calculation is carried out which produces 15,000 kg per year for the safety level of product sales. Management also targets a profit of Rp. 200,000,000 for the following year, namely 2024-2025, so to achieve this profit target, it must produce 26,145 kg.